The role of time gaps in determining the causal relationship between exchange rate and foreign exchange reserve in Sudan using Granger causality for the period 1980-2017 - Fadl, Hassan Tawakul Ahmed (Journal of Economic, Administrative and Legal Sciences, 2018)
The study of the relationship between economic variables requires tracking the variable or so-called phenomenon of the subject of the study) over time and for long periods, and the more time period when the results obtained good and accurate and an analysis almost explains the majority of factors affecting the phenomenon of the subject of the study and to clarify the impact of each period of time period The study of the effect of time factor on economic variables, where we find that the time gap affects the economic variables significantly and clearly, and this study aimed to show the role of time gaps on the study of the causal relationship Both the exchange rate and the foreign exchange reserve in Sudan, where the Granger test was applied to the data of the study, and found that the time gaps contribute to determining the form of causal relationship between exchange rate and foreign exchange reserves, Orbit and the need to re-examine the printing of the currency and the coordination between the amount of money supply and policies aimed at the exchange rate.